Moral distress, moral courage, and career identity among nurses: A cross-sectional study - Peng, Mengyun (Nursing ethics, 2023)
BackgroundThe concept of career identity is integral to nursing practices and forms the basis of the nursing professions. Positive career identity is essential for providing high-quality care, optimizing patient outcomes, and enhancing the retention of health professionals. Therefore, there is a need to explore potential influencing variables, thereby developing effective interventions to improve career identity.ObjectivesTo investigate the relationship between moral distress, moral courage, and career identity, and explore the mediating role of moral courage between moral distress and career identity among nurses.DesignA quantitative, cross-sectional study.MethodsA convenient sample of 800 nurses was recruited from two tertiary care hospitals between February and March 2022. Participants were assessed using the Moral Distress Scale-revised, Nurses’ Moral Courage Scale, and Nursing Career Identity Scale. This study was described in accordance with the STROBE statement.Ethical considerationResearch ethics approval was obtained from the researcher’s university and hospital where this study was conducted prior to data collection.FindingsMoral distress is negatively associated while moral courage is positively associated with career identity among nurses. Moral courage partially mediates the relationship between moral distress and career identity (β = −0.230 to −0.163, p < 0.01).DiscussionThe findings reveal a relationship between moral distress, moral courage, and career identity among nurses.ConclusionBy paying attention to nurses’ moral distress and courage, healthcare providers can contribute to the development of effective interventions to improve career identity, and subsequently performance, among nurses.